ANALISIS PENYUSUNAN LAPORAN KEUANGAN RUMAH MAKAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH - Nur Aina; Arifuddin; Safaruddin (Accounting Student Series on Emerging Trends, 2026)
This  research  was  conducted  at  Mama  Winda's  restaurant,  which  is  one  of  the MSMEs  in  Bombana  Regency.  This  study  aims  to  compile  financial  reports  based  on Micro,  Small  and  Medium  Entity  Financial  Accounting  Standards  (SAK  EMKM)  at Mama Winda's restaurant. This research use desciptive qualitative approach. Meanwhile, the  data  collection  methods  used  were  interviews,  documentation  and  literature  study. The  results  of  this  study  indicate  that  Mama  Winda's  restaurant  has  not  prepared financial  reports  in  accordance  with  SAK  EMKM  because  the  recording  of  financial reports is only in the form of recording purchase transactions such as purchases of raw materials, equipment, and equipment in its business activities. The obstacles faced so that SAK EMKM was not implemented in the preparation of financial reports were caused by two factors, namely internal factors and external factors.